ANALISIS EFEKTIVITAS PROGRAM KERJA TIM BASARNAS DALAM PENANGANAN BENCANA DI PROVINSI LAMPUNG TAHUN 2017 - Ida Farida (e-JKPP, 2019)
In analyzing the effectiveness of the BASARNAS Team work program, the author uses the effectiveness theory of the Agung Kurniawan Model which is used as a tool to measure the effectiveness of work programs. Agung Kurniawan's effectiveness consists of 3 (three) important variables, namely, Tasks and Functions, Operational Activities Plans, and Missions. By using these three variables can be seen how the effectiveness of the work program by the Lampung Province BASARNAS Team. This research was conducted using a type of qualitative research, with a qualitative descriptive approach / case study. Case studies are research on humans (can be a group, organization, or individual) and events / phenomena that occur in the community. Data collection in this study was obtained from interviews with several informants involved in the effectiveness of work programs for disaster management, observation and documentation. The results of this study are that the BASARNAS Team work program has not run effectively in disaster management in Lampung Province in 2017. This is indicated by operational activities / work programs that have not been adequate to support the spiritual health of the SAR Team, namely psychological infrastructure. In addition there are still some obstacles, namely the location of the BASARNAS which is quite far away so that respontime by the SAR Team makes it slow, the HR that does not have the potential to relieve the SAR Team burden, and the target of correctional activities is not achieved so that not all regions understand BASARNAS Lampung Province.